(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The establishment of forest plantations on rocky and eroded soils and slopes requires adequate soil preparation. Depending on the peculiarities of the terrain, requirements of the culture for afforestation, and according to the available technical means and organization of the work, different technological schemes can be applied for soil preparation. In this paper is conducted a study over the work of bulldozer and scarifying units for soil preparation of forest land for afforestation. Time study based on video records of all the operational processes for a working day was performed. These operational processes include aligning and clearing areas for afforestation, terracing slopes and primary tillage. Basic operational and economic indicators of the studied machines in certain operating conditions were established. Operational productivity, fuel consumption and the average cost per hectare of soil preparation with bulldozer, and uprooter, and ripping aggregate were finding. The average price per one hectare cleaning operation from shrubs with simultaneous alignment of the terrain, with frontal bulldozer DZ-27 and crawler T-170, with operational productivity 0.183 ha/hour, was defined on 332.9 €/ha. The average price per one hectare primary deep soil tillage by ripper D – 513 and crawler T–170, with operational productivity 0,076 ha/hour, was defined on 839,7 €/ha. The average price per one hectare machine terraces on terrains up to 28 °, constructed by universal bulldozer DZ-38 and crawler T–170 with operational productivity 0.064 ha/hour, was defined on 966.7 €/ha. It was performed an evaluation of the researched technological schemes. The results can serve for regulation of labor and fuel costs for the studied aggregates for soil preparation for afforestation of forest land.